FOXO3 gene hypermethylation and its marked downregulation in breast cancer cases: A study on female patients - Khan, Mohammad Aasif; Sadaf,; Ahmad, Irfan; Aloliqi, Abdulaziz A.; Eisa, Alaa Abdulaziz; Najm, Mohammad Zeeshan; Habib, Maria; Mustafa, Saad; Massey, Sheersh; Malik, Zoya; Sunita, Kumari; Pawar, Jogendra Singh; et al. (Frontiers in Oncology, 2023)
Background: FOXO3, a member of the FOX transcription factor family, is frequently described as being deregulated in cancer. Additionally, notable role of FOXO3 can be easily recognized in the process of ageing and survival. Even though various studies have been done to acknowledge the tumour-suppressive or oncogenic role of FOXO3 in cancer, still there exist a lack of understanding in terms of cancer prognosis and treatment. Therefore, to provide better insight, our study aims to evaluate the role and function of FOXO3 in breast cancer in Indian female patients. We examined the FOXO3 expression levels in breast cancer samples by analyzing mRNA and protein expression along with its clinicopathological parameters. Results: A total of 127 cases of breast cancer with equal normal cases (n=127) were assessed with methylation (MS-PCR), Immunohistochemistry (IHC), mRNA expression using Real-time PCR was analysed and 66.14% cases at mRNA level were found to be downregulated, while 81.10% of cases had little or very little protein expression. Our data state, the promoter hypermethylation of the FOXO3 gene and the downregulated protein expression are significantly correlated (p=0.0004). Additionally, we found a significant correlation between the level of FOXO3 mRNA with ER (p=0.04) and status of lymph node (p=0.01) along with this. Conclusion: Data suggests the prognostic significance and the tumour-suppressive role of FOXO3 in breast cancer cases studied in India. However, there is a need for the extended research targeting FOXO3 to measure its clinical potential and develop well-defined therapeutic strategies.